2009
DOI: 10.1016/j.asj.2008.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Centrifugation Technique and Effect of Epinephrine on Fat Cell Viability in Autologous Fat Injection

Abstract: Centrifugation with 3000 RPM for 3 minutes is recommended. The effect of epinephrine on fat cell viability is negligible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…Pu et al [44] showed that the Coleman technique yields a great number of viable adipocytes and sustains a higher level of cellular function within harvested fat grafts than conventional methods. Kim et al [30] evaluated the optimal speed and duration of centrifugation for processing fat grafts, concluding that centrifugation at 3,000 rpm for 3 min is optimal for adipocyte survival. Yoshimura et al [45] reported that centrifugation of aspirated fat efficiently concentrates adipocytes and ADSCs and eliminates water content in the graft material, which may disturb the adherence of ADSCs to the adipose tissue and interfere with differentiation into expected lineages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pu et al [44] showed that the Coleman technique yields a great number of viable adipocytes and sustains a higher level of cellular function within harvested fat grafts than conventional methods. Kim et al [30] evaluated the optimal speed and duration of centrifugation for processing fat grafts, concluding that centrifugation at 3,000 rpm for 3 min is optimal for adipocyte survival. Yoshimura et al [45] reported that centrifugation of aspirated fat efficiently concentrates adipocytes and ADSCs and eliminates water content in the graft material, which may disturb the adherence of ADSCs to the adipose tissue and interfere with differentiation into expected lineages.…”
Section: Discussionmentioning
confidence: 99%
“…At this writing, Coleman's technique has been increasingly applied worldwide although often altered by personal modifications. In recent years, many authors have compared the products of different processing methods including sedimentation by gravity [28], washing [28], centrifugation [29][30][31][32][33], and filtering techniques [34][35][36], but their experimental studies have evaluated only single parameters (i.e., cell viability or cell enrichment), leading to biased appraisal of this crucial issue. Thus, the results still are controversial, and surgeons do not currently agree on which method is best for processing fat grafts before clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate centrifugation condenses tissue and ASCs, and also improves fat graft survival, although too strong centrifugation may worsen graft survival. 13,14 There are some other attempts to further condense adipose graft tissue. Mechanical chopping, shredding, pureeing, or mincing, manually or with specific devices (like homogenizers or food processors), can further fragment aspirated fat tissue and rupture adipocytes.…”
Section: Adipose-derived Stem/stromal Cells Condensation By Reductionmentioning
confidence: 98%
“…The degree of adipocyte destruction differs among patients, but only minor differences in percentage of cell destruction have been shown among the different centrifugal forces, while a great variability is demonstrated among patients . In our setting, we used centrifugation conditions comparable to that considered optimal for obtaining good results in adipose transplantation (Kim et al 2009). To further overcome the mechanical injury of fat tissue, the Prolipostem® kit was equipped with a special vacuum syringe that allows the aspiration of fat without the use of pneumatic pumps.…”
Section: Discussionmentioning
confidence: 99%